Supporting parents following childhood traumatic brain injury: a qualitative study to examine information and emotional support needs across key care transitions. (4th July 2014) - Kirk, S.; Fallon, D.; Fraser, C.; Robinson, G.; Vassallo, G.
Abstract Introduction Traumatic brain injury (TBI) is the leading cause of death and acquired disability in childhood. Research has demonstrated that TBI can lead to long‐term physical, cognitive, emotional and behavioural difficulties for children and parental stress. Less is known about how parents experience a childhood brain injury and their information and support needs. This study aimed to examine parents' experiences and support needs following a childhood TBI from the time of the accident to their child's discharge home. Methods Qualitative semi‐structured interviews were conducted with 29 parents/carers of children who had experienced a severe TBI. Participants were recruited from one children's tertiary centre in the UK. Data were analysed using the Framework approach. Results Parents had unmet information and emotional support needs across the care trajectory from the time of the accident to their child's return home. Information needs related to the impact of the TBI on their child; current and future treatment/rehabilitation plans; helping their child and managing their behaviour; accessing services/support. They lacked information and support for care transitions. In different settings parents faced particular barriers to having their information needs met. Parents' felt they needed emotional support in coming to terms with witnessing the accident and the loss of their former child. Lack of community support related not only to service availability but to a general lack of understanding of the impact of TBI on children, particularly when this was invisible. Overall parents felt unsupported in coping with children's behavioural and psychological difficulties. Discussion Taking a holistic approach to examining parents' experiences and support needs has enabled their changing needs to be highlighted across key care transitions within hospital and community settings and the service implications identified. Improvements in care co‐ordination across care transitions are needed to ensure continuity of care and integration of support.